History of Educational Psychology Figures Who Shaped Modern Education - Weni Massang (Yayasan Baru Haji Samsudin, 2025)
This study examines the foundational contributions of seven influential figures in educational psychology whose theories have significantly shaped contemporary understandings of learning and cognitive development. The figures discussed include Jean Piaget, whose theory of cognitive development emphasizes developmental stages of thinking; Lev Vygotsky, who introduced the sociocultural theory highlighting the role of social interaction and culture in learning; and B.F. Skinner, a key proponent of behaviorism and programmed learning focused on observable behavior and reinforcement. Additionally, the study explores Jerome Bruner’s theory of discovery learning, which stresses active learner engagement; John Dewey’s philosophy of learning by doing, which connects education with real-life experiences; Howard Gardner’s theory of multiple intelligences, which broadens the concept of human ability beyond traditional measures; and David Ausubel’s theory of meaningful learning, emphasizing the importance of prior knowledge in the learning process. By analyzing these theories collectively, the study illustrates how each perspective contributes uniquely to understanding how individuals learn and develop. Together, these approaches offer a comprehensive framework encompassing cognitive, social, behavioral, and constructivist viewpoints. The integration of these theories provides valuable insights for educators and curriculum designers seeking to implement effective, learner-centered educational practices.